The Impact of HIV Infection on the Population’s Quality of Life in Regions - Baskakova, Irina Vladimirovna; Podymova, Anzhelika Sergeevna; Turgel, Irina Dmitrievna; Balandina, Marina Sergeevna (Economy of Regions, 2020)
Assessment of quality of life of patients with HIV infection is of great importance due to the unfavourable epidemic situation with this disease both in the Russian Federation in general and in the Sverdlovsk region. This chronic disease, accompanied by long-term therapy and medical supervision, has adverse effects on lives of people carrying HIV/AIDS. Additionally, it negatively impacts the functioning of all spheres of the society. In the autumn of 2018, we studied the populations quality of life in the Sverdlovsk region using the methodology of the World Health Organization (the WHOQOL-26 questionnaire). This questionnaire considers quality of life as an integral characteristic of physical, psychological, emotional, and social functioning of a healthy or sick person based on subjective perception. We added specific questions in the questionnaire to assess how the quality of life of a person with a positive HIV status changes depending on whether the respondent receives antiretroviral therapy. The sample included patients visiting branches of the Sverdlovsk Regional Center for Prevention and Control of AIDS. The quality of life of the survey participants was assessed in four dimensions: physical health, psychological well-being social connections and the environment. The majority of HIV patients assess their quality of life and health by means of averages. However, according to the “physical health” and “social well-being” measurements, the quality of life of people living with HIV/AIDS is lower than in the control group of healthy respondents. The study’s residts demonstrate the importance of developing and implementing a program of professional and socio-economic rehabilitation for people who carry HIV/AIDS to maintain social functioning and optimal quality of life.